2016
DOI: 10.1177/0017896916653429
|View full text |Cite
|
Sign up to set email alerts
|

Promoting health literacy in the classroom

Abstract: Objective: Research has shown that developing health literacy in early life is critical to reducing lifestyle-related diseases, with schools being identified as central settings for this purpose. This paper examines how one classroom-based health educational programme, IMOVE, helped Danish primary school pupils develop health literacy related to physical activity. It discusses curriculum-integrated health education’s contribution to promoting health literacy. Design: Qualitative classroom observation. Setting:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 26 publications
0
58
0
5
Order By: Relevance
“…Thus, the step data collection was handled by students with little or no support from teachers. This procedure produced student ownership 21 and made the data collection feasible in a school setting, where the class had different teachers during the day, and students often started and ended their school day in different classrooms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the step data collection was handled by students with little or no support from teachers. This procedure produced student ownership 21 and made the data collection feasible in a school setting, where the class had different teachers during the day, and students often started and ended their school day in different classrooms.…”
Section: Methodsmentioning
confidence: 99%
“…This study showed that IMOVE contributed to the development of physical activity-related health literacy in students. 21 The present study examined the step data collected by the students who took part in the classroom observational study.…”
mentioning
confidence: 99%
“…The teacher's guides indicate the procedures for each lesson. IMOVE was developed and evaluated earlier with respect to its potential to foster participation and enhances reflection concerning physical activity [33,34]. The material is available in English on the IMOVE website [35].…”
Section: Journal Of Food and Nutrition Research Action And Change Procementioning
confidence: 99%
“…The IMOVE program was developed and tested earlier and found to be suitable to promote learning on physical activity integrated into maths [33][34][35]43].…”
Section: Developing and Testing The Intervention Componentsmentioning
confidence: 99%
“…National Action Plans in numerous countries recommend focusing on public schools as an ideal setting to enhance health literacy early in the lifespan [12][13][14], including in Germany [7,15]. However, public schools are often not well prepared to handle health related problems and promote health literacy or healthy behavior in the classroom or the broader school environment [16].…”
Section: Introductionmentioning
confidence: 99%